A Scapular Spine Fracture Defined on the Basis of a Bisphosphonate: a Case Report and Review of the Literature - Ilyas, G; Senyuva, G (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
Bisphosphonates are commonly used in the treatment of osteoporosis. Long-term use without drug holiday causes the risk of atypical fractures. Subtrochanteric and femoral stress fractures are among the frequently described complications. In our case report; a stress fracture of the scapular spine, a previously undescribed adverse effect of bisphosphonates, is presented. Key words: bisphosphonates, scapular spine, stress fracture, drug holiday.
Keywords: Spinal Fractures; Diphosphonates; Femoral Fractures; Shoulder Fractures; lidé; fraktury páteře; bisfosfonáty; fraktury femuru; inhibitory kostní resorpce; fraktury proximálního humeru; Fractures, Stress; Humans; stresové fraktury; Bone Density Conservation Agents